Vertical-junction photodiodes for smaller pixels in retinal prostheses. (16th March 2021) - Huang, Tiffany W; Kamins, Theodore I; Chen, Zhijie Charles; Wang, Bing-Yi; Bhuckory, Mohajeet; Galambos, Ludwig; Ho, Elton; Ling, Tong; Afshar, Sean; Shin, Andrew; Zuckerman, Valentina; Harris, James S; et al.
Abstract: Objective. To restore central vision in patients with atrophic age-related macular degeneration, we replace the lost photoreceptors with photovoltaic pixels, which convert light into current and stimulate the secondary retinal neurons. Clinical trials demonstrated prosthetic acuity closely matching the sampling limit of the 100 μ m pixels, and hence smaller pixels are required for improving visual acuity. However, with smaller flat bipolar pixels, the electric field penetration depth and the photodiode responsivity significantly decrease, making the device inefficient. Smaller pixels may be enabled by (a) increasing the diode responsivity using vertical p–n junctions and (b) directing the electric field in tissue vertically. Here, we demonstrate such novel photodiodes and test the retinal stimulation in a vertical electric field. Approach. Arrays of silicon photodiodes of 55, 40, 30, and 20 μ m in width, with vertical p–n junctions, were fabricated. The electric field in the retina was directed vertically using a common return electrode at the edge of the device. Optical and electronic performance of the diodes was characterized in-vitro, and retinal stimulation threshold measured by recording the visually evoked potentials in rats with retinal degeneration. Main results. The photodiodes exhibited sufficiently low dark current (<10 pA) and responsivity at 880 nm wavelength as high as 0.51 A W −1, with 85% internal quantum efficiency, independent of pixel size. Field mapping in saline demonstrated uniformity of the pixel performance in the array. The full-field stimulation threshold was as low as 0.057 ± 0.029 mW mm −2 with 10 ms pulses, independent of pixel size. Significance. Photodiodes with vertical p–n junctions demonstrated excellent charge collection efficiency independent of pixel size, down to 20 μ m. Vertically oriented electric field provides a stimulation threshold that is independent of pixel size. These results are the first steps in validation of scaling down the photovoltaic pixels for subretinal stimulation.